Perceived Godfatherism, Political Awareness and Voting Behaviours in Nigeria: A Clarion Call to All Prospective Electorates. - Lawal, Abiodun Musbau; Adeleke, 2Adebayo Ibrahim (Advances in Social Sciences Research Journal, 2015)
Poor leadership in Nigeria is making her citizens to lose interest in the electoral system and governance in the country. The study examined ethnicity, religion, perceived godfatherism and political awareness as predictors of voting behaviour among electorates in Nigeria. This was a survey research where ex-post facto research design was adopted. Data were collected via structured questionnaires; and 473 participants were sampled using accidental sampling selection method. Hypotheses stated in the study were tested using multiple regression and t-test for independent samples. Results revealed that all the predictor variables jointly predicted electorates’ voting behaviour. However, perceived godfatherism and political awareness independently contributed in explaining voting behaviour of electorates. Male electorates were not significantly different in voting behaviour from female electorates. It is concluded that electorates in Nigeria see the presence of godfatherism and being informed about the political processes as relevant to exercising their civic rights. It is recommended that issue of godfatherism should be abated and political awareness should be intensified to ensure higher voting behaviour in Nigeria.